A poorly known species and new records of Plecoptera from the Eastern Tien Shan, Xinjiang Uygur Autonomous Region, China - Teslenko, Valentina A.; Palatov, Dmitry M. (Zootaxa, 2021)
Nemoura lepnevae Zhiltzova, 1971, Amphinemura mirabilis turkestanica Zhiltzova, 1978, Capnia s.l. longicauda Zhiltzova, 1969 and Mesoperlina pecirkai Klapálek, 1921 are reported for the stonefly fauna of China for the first time. The species were collected in the Bogdo-Ula and Karlyktag Ranges of the Eastern Tian Shan Mountains, the Xinjiang Uygur Autonomous Region. In addition, a detailed redescription of Filchneria wusuensis Chen, 2019 including new illustrations is provided.